The Aurantii Fructus Immaturus flavonoid extract alleviates inflammation and modulate gut microbiota in DSS-induced colitis mice - Chen, Si-Yuan; Zhou, Qing Yi-Jun; Chen, Lin; Liao, Xin; Li, Ran; Xie, Tao (Frontiers in Nutrition, 2022)
Inflammatory bowel disease (IBD) is a chronic, relapsing immune-mediated disease that always leads to a progressive loss of intestinal function. Therefore, it is important to find potential therapeutic drugs. This study was conducted to elucidate the effect of Aurantii Fructus immaturus flavonoid extract (AFI, 8% neohesperidin, 10% naringin) on DSS-induced intestinal inflammation and the gut microbiome. To explore the mechanism of action by which AFI protects against intestinal inflammation, a total of 50 mice were randomly divided into 5 groups [CG (control group), MG (model group), AFI low dose, AFI middle dose, and AFI high dose] and received 2.5% DSS for 7 days. Then, mice in the AFI groups were orally administered different doses of AFI for 16 days. The results showed that, compared with the MG group, the food intake and body weight were increased in the AFI groups, but the water intake was lower. Additionally, AFI significantly alleviated DSS-induced colitis symptoms, including disease activity index (DAI), and colon pathological damage. The levels of IL-6, IL-1β and TNF-α in serum and colon tissue were significantly decreased. The diversity and abundance of the intestinal microbiota in the AFI group were decreased. The relative abundance of Bacteroidota was increased, and the relative abundance of Firmicutes was decreased. AFI plays an important role in alleviating DSS-induced intestinal inflammation and regulating Oscillospira, Prevotellaceae and Lachnospiraceae in the intestine at low, medium and high doses, respectively. This report is a pioneer in the assessment of AFI. This study not only demonstrated the anti-inflammatory activity of AFI but also identified the microbiota regulated by different concentrations of AFI.